BUSINESS MODEL CANVAS: A STRATEGY TO BUILD COMPETITIVE ADVANTAGE - Sirine, Hani; Setyawan, Michael Eden Allan (Merwin Publisher, 2024)
Economic developments in Indonesia make competition in business stronger. This study aims to find out the business Model Canvas looks like at Café Kupi Haus in Ajibarang, and to find out how the strategy of the business model is to build a competitive advantage. This study uses a qualitative approach by conducting interviews with the owners, employees and customers of Kupi Haus Ajibarang. The result of this research is that the Competitive Advantage in Kupi Haus Ajibarang comes from Value Propositions ranging from offering a variety of menu variants, strategic locations, and complete facilities, and also having a complete and sophisticated coffee machine with almost three years of experience in serving coffee. makes Kupi Haus superior to the cafes around Ajibarang.